An Empirical Study on Job Satisfaction and Employee Turnover in Cell Phone Servicing Companies: Bangladesh Context - NAWAZ, Faraha (Asian Journal of Empirical Research, 2013)
This paper aims to analyze the critical factors that lead to job dissatisfaction and high employee turnover at cell phone servicing companies in Bangladesh. The Nokia Care was chosen from three big mobile phone servicing companies as a case study to understand the grounds and factors leading to high employee turnover in mobile phone servicing companies in Bangladesh. The study reveals that the managers’ mind set and management policy are more consistent with Taylor’s scientific theory. According to Taylor employees are likely to work harder when they are being pressurized and supervised closely to ensurethe maximum expected output from them.Employees in Nokia Care are regarded as unreliable by their senior managers who develop strategies that they consider to be the ’one best way’ for carrying out jobs throughout the organization. Management also believes that for optimum results job roles should be divided into several tasks that are carried out by different employees.The study also reveals their preference for the right person and the right tool for performing any task. On the other hand, employees’ viewpoints are different to the managers; they often possess an indifferent mentality to their work and most of the employees do not consider working in Nokia Care as their long term future career. Some employees argue that it’s better to do be doing something rather than be doing nothing. Despite the few amenities provided by the company, employees are still displeased with their salaries and any rewards given as incentives and they regard their working conditions as being unfair.